Strategi Konten Media Sosial untuk Meningkatkan Interaksi: Studi Facebook Hotel Masa Inn - Pratiwi, Ni Luh Sinta; Intentilia, Anak Agung Mia (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This research aims to understand the role of social media content strategy in increasing customer engagement, by taking the Facebook Masa Inn Hotel social media case study as its main digital communication platform. The focus of the research is on the consistency of the shared content and its ability to build closeness with the audience. The research method used is qualitative descriptive, with data collected through in-depth interviews with social media managers, direct observation of content activity on Facebook, as well as documentation of posts and customer interactions. Research results show that consistency in sharing daily content, such as guest activities and hotel events, can create natural engagement through the active participation of customers who also share experiences and mark the hotel's official account. However, Masa Inn Hotel's social media management is still limited due to the lack of a structured content calendar and optimization strategies based on analytical data. Even so, the warm interaction built on Facebook is a major factor in strengthening customer loyalty and expanding the hotel's positive image in the digital world.